Laparoscopic Repair of Bochdalek Hernia: A Rare Presentation of Abdominal Pain in the Elderly - Christopher Steen; Jia Hui Lee; Enoch Wong; Sean Mackay (Case Reports in Surgery)
Bochdalek hernias (BHs) are rare, and the presentation, diagnosis, and management of them can be complex. We present a 70-year-old man presenting with left flank pain who underwent a successful laparoscopic repair of BH with mesh placement.